2015
DOI: 10.17795/jjcdc-30508
|View full text |Cite
|
Sign up to set email alerts
|

Depression, Functionality and Adaptability of Elderly Patients After Open Heart Surgery Off- or On-Pump

Abstract: Background:Open heart surgery is performed by two methods of off or on cardiopulmonary bypass. Both methods may affect the rate of depression, level of functionality and adaptation of the elderly undergoing the operations. Objectives: The current study aimed to assess depression, level of functionality and adaptability in elderly patients undergoing open heart surgery with off or on pump in the in open heart surgery intensive care unit of Imam Khomeini and Shariati Hospitals, Tehran University of Medical Scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Previous reports have indicated that the world's aging population will increase from 200 million in 1950 to 1100 million in 2025 [1]. Currently, Iran, like other countries around the world, has undergone considerable changes in the age structure of its population as a result of reduced fertility and increased life expectancy in the past few decades [4, 5]. According to statistics, the proportion of the elderly population has increased from 6.6% in 1996 to 9.2% in 2016 [6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have indicated that the world's aging population will increase from 200 million in 1950 to 1100 million in 2025 [1]. Currently, Iran, like other countries around the world, has undergone considerable changes in the age structure of its population as a result of reduced fertility and increased life expectancy in the past few decades [4, 5]. According to statistics, the proportion of the elderly population has increased from 6.6% in 1996 to 9.2% in 2016 [6].…”
Section: Introductionmentioning
confidence: 99%
“…In today’s world, the concept of active aging has been introduced; meaning, with the increasing number of the elderly population, their quality of life should also be considered, the aim of supporting the elderly has not be limited only to increase their life expectancy (longevity) ( 7 ). Quality of life as one of the most important concepts, has come to the focus of interest of international organizations such as the World Health Organization (WHO) ( 8 ). The WHO has defined the quality of life as the individuals’ understanding of their situation in life regarding the culture, the value system in which they live, their goals, expectations, standards and priorities ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, like many other developing countries, Iran's population is experiencing fundamental and significant changes in its age structure following the constant fertility reduction and the increased life expectancy. These changes require important economic and social considerations regarding policy making and planning [3][4].…”
Section: Introductionmentioning
confidence: 99%